2016
DOI: 10.1136/jclinpath-2016-203862
|View full text |Cite
|
Sign up to set email alerts
|

Dysfibrinogenemia-associated novel heterozygous mutation, Shanghai (FGAc.169_180+2 del), leads to N-terminal truncation of fibrinogen Aα chain and impairs fibrin polymerization

Abstract: Fibrinogen Shanghai results in N-terminal truncation of Aα chain, which does not interfere with synthesis, assembly or secretion of fibrinogen, but compromises fibrin polymerization and clot formation. APS at least partially contributes to the development of thrombosis in the propositus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Routine coagulation tests, including prothrombin time, activated partial thromboplastin time, thrombin time and the fibrinogen activity, were carried out with citrated plasma samples on a Sysmex-7000 coagulation analyser. Thrombophilia screening tests, including the activities of PC, PS and antithrombin, as well as lupus anticoagulant, anticardiolipin antibody, anti-β2 glycoprotein 1 and total homocysteine, were assayed as described previously 23. The qualitative analysis of total PS (TPS) level in plasma were detected by western blot using a rabbit polyclonal anti-human PS antibody (Abcam, Cambridge, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Routine coagulation tests, including prothrombin time, activated partial thromboplastin time, thrombin time and the fibrinogen activity, were carried out with citrated plasma samples on a Sysmex-7000 coagulation analyser. Thrombophilia screening tests, including the activities of PC, PS and antithrombin, as well as lupus anticoagulant, anticardiolipin antibody, anti-β2 glycoprotein 1 and total homocysteine, were assayed as described previously 23. The qualitative analysis of total PS (TPS) level in plasma were detected by western blot using a rabbit polyclonal anti-human PS antibody (Abcam, Cambridge, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Scanning electron microscopy observations of the fibrin from the proband suggested that the strength, structure, and stability of fibrin might be impaired. Consequently, the clot formed by such fibrin is more permeable and less likely to effectively entangle platelets and other blood cells, resulting in reduced hemostasis and an elevated risk of bleeding compared to healthy individuals [ 11 ].…”
Section: Methodsmentioning
confidence: 99%